Cleaner production: a brief review on definitions, trends and the importance in environment protection. - Hadibarata, Tony; Chia, Xing Kai (Environmental and Toxicology Management, 2021)
There are several environmental issues caused by economic growth and urbanization, such as soil degradation, water scarcity, deforestation, and biodiversity extinction. To solve these environmental problem issues, cleaner production (CP) had presented as account to reduce waste generation, energy usage and environmental pollution.CP concept was accepted and applied on many industrial sectors. Based on the current trend, CP is shifting to tackle global environmental problems by focusing on reducing carbon emission and resources consumption. In this paper, implementation of CP was presented such as waste and pollutants reduction, process and products efficiency improvements, and risk reduction towards human and environment. Overall, CP is an effective tool not only in environmental protection, but also in company management as it can increase the profit gains, reduce resources consumption, reduce pollutants emission and protects the safety of staff and workers.